The Influence of Sintering Temperature toward Density and Strength of Plastic-Ruber Composite - Heru Sukanto (Jurnal Energi Dan Manufaktur, 2009)
The research investigates the effect of sintering temperature on density and mechanical properties of HDPE-rubbercomposite which was produced by pressured sintering methodThe materials that were used are HDPE plastic waste of oilbottle and unused tire. These materials were powdered via mechanical grinding manually. The powder size of -20 mesh wasselected as a raw material for specimen. Producing the specimens involved powder technology. Pressured sintering processwas commited for 5 minutes under pressure load of 1 MPa. The sintering temperature was variated along 110 to 140oC byincreasing 10oC incrementally. Specimen testing involved density, bending strength and izot impact strength. All of testingwas conducted on ASTM standard testing.The result reveals that increasing sintering temperature will grow up the density,bending strength and impact strength of specimen up to 10%, 12% and 72% respectively. The extreme increasing ofspecimen properties occurs at the temperature range of 120 to 130oC..